PADAT KARYA SEBAGAI KONTRIBUSI KEHIDUPAN MASYARAKAT PADA PENGGUNAAN DANA DESA (Studi Kasus Desa Kaneyan Kecamatan Tareran Kabupaten Minahasa Selatan) - Manembu, Roni Ritonga; Kusen, Albert W. S.; Deeng, Djefry (HOLISTIK, Journal Of Social and Culture, 2019)
The problem of unemployment and poverty is a crucial problem for a village, at the micro level, development (modernization) has encouraged the social mobilization of the villagers. However, a number of goals in social mobilization did not occur evenly. The development itself turned out to not be a solid foundation for social transformation, even the results of village development in the present era did not show sustainability, or even tended to experience roads in place (involution). Various government assistance programs that flow to the villages have not significantly been able to lift the livelihoods of village people, fight village poverty, prevent urbanization, and provide employment and others. What happened was the dependence, conservatism and pragmatism of villagers on government assistance.The government, through the Coordinating Minister for Human Development and Culture, provides advice to focus on labor-intensive sectors. One labor intensive program is an infrastructure project, which includes roads and bridges involving local communities. Basically, labor intensive is a work based on the utilization of available labor (in large quantities) and project development activities that use more human power compared to capital or machinery. This is solely for the sake of opening jobs, while increasing the welfare and purchasing power of the people. To support the acceleration of poverty alleviation and reduce unemployment in rural areas.Based on the results of research and observations, cash for work programs that use the Village Fund, where a project in Kaneyan village is carried out in a self-managed manner and project workers are paid daily or weekly. Thus, the Village Fund is not only used to buy infrastructure materials, but also to pay honorarium for workers involved in the construction itself. The community participation in the development phase 1) Decision-making stage; 2) Implementation stage; 3) Stage of enjoying the results; 4) Evaluation Phase;Keywords: Labor Solidarity, Participation, Village Funds